A new insight on the decreasing sea level trend over the Ionian basin in the last decades - Del Río Vera, Jorge; Criado-Aldeanueva, Francisco; García-Lafuente, Jesús; Soto-Navarro, Francisco Javier (Elsevier, 2009)
Altimetry measurements over the Ionian region and tide gauge records along the southern Italian coasts have been combined to analyse the negative sea level trend over the Ionian basin in the last decades. The apparent decreasing trend should be better understood as an abrupt sea level drop in 1998 probably linked to changes in the surface circulation in the Ionian basin induced by the Eastern Mediterranean Transient, which changed from anticyclonic to cyclonic about March 1998. From then onwards, a rising rate of 7.9 ± 0.9 mm/year is observed over the basin.
Se adjunta la versión postprint aceptada, que incluye las correcciones de de los revisores, debido a que la editorial tiene los derechos de copyright y no permite la difusión en acceso abierto de la versión publicada. Puede accederse a la misma a través del DOI que se incluye en los datos de la publicación.
Keywords: Nivel del mar - Italia; Sea level trends; Altimetry and tide gauge records; Esatern Mediterranean Transient; Ionian Sea